Mary Barton - Gaskell, Elizabeth Cleghorn, 1810-1865 (Floating Press, 2009)
The first novel by English writer Elizabeth Gaskell, Mary Barton was published in 1848. It tells of the plight of the lower class in Manchester during the 1830s and 1840s. Contrasting the gap between rich and poor, the first half of the novel tells of the humble lives of the Barton and Wilson families, the extreme poverty of the Davenports and the luxurious life of the Carsons. Symbolically, John Barton receives five shillings for selling most of his worldly possessions; Henry ...